Analisis Stabilisasi Tanah Lempung Dengan Menggunakan Ampas Kopi Dan Arang Kayu Terhadap Nilai CBR - Anggareksa, Tenri Angka Arya; Yusuf, A. Rumpang; Cangara, Satriawati (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Considering that almost all buildings are built on or on the surface of the land, the land must have resistance to the building or the forces that work through the building by stabilizing the quality of the soil. This research aims to analyze the effect of using coffee grounds and wood charcoal on the geotechnical properties of clay soil. The main focus of the research is on changes in the Unsoaked CBR (California Bearing Ratio) value of clay soil due to the addition of coffee grounds and wood charcoal, both of which have binding properties such as coffee grounds which contain organic C (44.87%), N. (1.69%), K(2.49%), Na(0.04%), P(0.18%), pH (5.6) and wood charcoal can improve water and air circulation so that it can bind carbon and reduces soil swelling and shrinkage. The experimental method was used by mixing 10% wood charcoal and variations of coffee grounds 5%, 10% and 15% into clay soil samples. The results of testing the soil characteristics showed that the soil according to AASHTO was clay soil. Meanwhile, according to the USCS classification, this soil is included in the CH category (high plasticity inorganic clay). The results of the research showed that adding 10% Wood Charcoal to the original soil could increase the CBR value by 23.91%, while in the Wood Charcoal variation with the addition of Coffee Grounds by 5%, 10% and 15%, the CBR value decreased by 18.42%. 15.38%, and 9.57%.